Mixed fibers diet in surgical ICU septic patients - Kaweesak Chittawatanarat (2018)
Diarrhea commonly occurs in surgical critically ill patients, especially septic patients and fiber formulas have been reported to improve diarrhea. Most reports have used soluble or insoluble fiber exclusively, while the effects of a mixed fiber diet remain unclear. This study compares diarrhea scores between mixed-fiber and nonfiber diets in surgical septic patients receiving broad spectrum antibiotics. We conducted a prospective randomized control double blind study in a general surgical ICU. Patients who received broad spectrum antibiotics and no contraindication to enteral feeding were randomly allocated to a fiber or non-fiber diet for up to 14 days. Nutritional delivery and diarrhea scores were recorded daily. Intention to treat analysis was performed. Thirty-four patients were enrolled in the study, 17 in the fiber group and 17 in non-fiber group. These two patients groups were similar in demographics, disease severity, nutritional status, cause of sepsis and total feeding per day. The proportion of patients with diarrhea score ≥12 was higher in the non-fiber group than in the fiber group, but the difference was not statistically significant [8/17 (47.06%) vs. 4/17(23.53%); p=0.15]. However, the fiber group had a lower mean diarrhea score (fiber vs. non-fiber = 3.6 ± 2.3 vs. 6.3 ± 3.6; p=0.005), as well as a lower global diarrhea score from the generalized estimation equation model for repeated measurement [Coefficient -3.03 (95%CI= -5.03 to -0.92); p=0.005]. In summary, a mixed fiber diet formula can reduce the diarrhea score in surgical critically ill septic patients who received broad spectrum antibiotics.